O matrimônio cristão diante da realidade contemporânea - Delfino, Claudio Antonio (2014)
The focal point of this research is to reflect on the Christian marriage in the current reality. For that purpose we define as the primary hypothesis of our research to check which are the main theological-pastoral prospective of the Church to guide the experience of Christian marriage, given the unstable and complex contemporary reality. In order to do what was proposed in this primary hypothesis, we established three secondary hypotheses, corresponding to each of the chapters in this way: a) to critically analyze the contemporary reality from pre-established principles, showing how it can interfere with the way of being and thinking of the people, especially within the marriage and family life, requiring from the Church in its mission of evangelization, responses to new emerging aspirations; b) to present the fundamental notes of Christian marriage, basing on the biblical and theological foundations of this; c) to detect the major theological-pastoral prospective of the Church to guide the experience of Christian marriage, given the unstable and complex contemporary reality, based on what we presented in the previous two chapters. We believe that the importance of these considerations consist in the fact that we have to continually reaffirm the fundamental human and Christian values of marriage and family, especially at a time when we experience a phenomenon called change of season. The Church, in its mission to evangelize, cannot ignore the changing needs and challenges that people experience in their marriage and family life every day. Fidelity to Jesus Christ and sensitivity with the joys and hopes, sorrows and sufferings of men and women of our time, are two sides of the same coin that the Church cannot ignore. At the end of our research we concluded that the main theological-pastoral prospective that the Church must implement in the orientation of marriage and family life are as follows: the need to examine in depth though faith and reason its ecclesial comprehension of the reality of marriage and family; to promote a sincere pastoral conversion, from a mere maintenance pastoral to an authentically missionary pastoral; need to strengthen and innovate a missionary Family Ministry